Adenomyoepithelial adenosis mimicking phylloides: A diagnostic dilemma - Jyoty Singh; Atin Singhai; Suresh Babu; Kulranjan Singh; Anand Mishra (Indian Journal of Pathology and Microbiology)
Benign proliferative breast diseases are well recognized in young females. Benign biphasic proliferation of epithelial and myoepithelial cells has been observed, among which adeno-myoepithelial adenosis is one of the rare morphologies published in the literature with the tendency to recur and poses a risk for low-grade malignant transformation. Here, we report a case of a young female who had a history of recurrent breast lump mimicking phyllodes tumor and eventually diagnosed as adeno-myoepithelial adenosis on histopathological examination.